(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article describes the volunteer programs of the Special Olympics, which are implemented in the regions of Europe and Eurasia. The goal is to present the content of volunteer programs of the Special Olympics and to investigate their distribution in the regions of Europe and Eurasia. Research materials and methods. Theoretical analysis of scientific and pedagogical literature; Internet resources methods of statistical processing of received information. The volunteer programs of the Special Olympics of Europe and Eurasia (58 regions) were studied. It has been established that there are three types of Special Olympics programs: educational; parallel; national Training is aimed at mastering movement skills in the chosen sport. Educational programs include motor activity training programs, a program for young athletes, and combined sports. These are inclusive programs that are designed to bring together athletes with and without disabilities and their families for various sports events. Parallel aimed at supporting the health of athletes with disabilities is the "healthy athletes" program, which is implemented in the following directions: "Health promotion", "Leg health", "Joy of being healthy", "Healthy ears", "Open eyes", "Healthy smile", "MedFest", "Strong mind". National programs pay more attention to the competitive activities of athletes with mental disabilities. The study characterized the content of volunteer programs on the example of the regions of Europe and Eurasia. It was found that SO programs are gradually spreading in the countries of Europe and Eurasia. The introduction of such programs and constant volunteer support definitely contributes to the better integration of people with disabilities into society, improves their physical and mental health. In view of this, the experience of countries that have achieved significant success, such as Great Britain, Germany, and Greece, is significant.